FRI0440 Lupus Clinical Trials: A Systematic Review of the Landscape and Opportunities for Improvement. (10th June 2014) - Goel, N.; van Rijen, E.; Hillier, J.; Hepburn, R.; Duncan, A.
Abstract : Background: In the last decade, the number of new drugs in development for the treatment of systemic lupus erythematosus (SLE) and related indications, e.g., lupus nephritis (LN) has been increasing. Belimumab's approval for the treatment of SLE in 2011 in the U.S. and EU, eliminated some regulatory uncertainty around SLE drug development. Trials of SLE, an uncommon and heterogeneous disease with complex assessment tools, demand investigator experience with the disease state and its management. Slow recruitment of clinical trials impacts their conduct, introducing confounders as treatment practices change over the development program. These factors increase costs and decelerate programs for SLE drug development, impeding the rate of new drug approvals to address unmet medical need. Objectives: We performed a systematic review of ClinicalTrials.gov (CT.gov ) and the literature to assess the evolution of the lupus trial landscape during the last 10 years and its current status. Methods: A systematic search was conducted of CT.gov and PubMed to identify lupus studies with a start date of Jan 2004 through Dec 2013. Studies where lupus subjects were only a subset of the targeted population were excluded as well as studies which were withdrawn or terminated prior to enrolling. In Sep 2007, legislation was passed that required that most interventional trials in the US be registered on CT.gov, which had been voluntary prior to this date. An emphasis therefore was placed on evaluating trials posted with a start date of 1 Jan 2008 or later. Results: The table summarizes the lupus studies registered on CT.gov over the last 10 years. Of these, 166 were identified with a start date between Jan 2008 and Dec 2013. Listed indications included SLE (63%), LN (23%), cutaneous lupus erythematosus (CLE) (9%), discoid lupus erythematosus (DLE) (3%), or mixed lupus conditions (2%). Approximately half of the studies were in early development (Phase 1, 1/2, or 2, 47%) and/or industry-sponsored (56%). The number of lupus studies started per year remained reasonably stable for both academic and industry sponsored studies (24 in 2008, 26 in 2013). The number of targeted patients increased from 3280 in 2008 to 7057 for studies started in 2013, driven mainly by industry-sponsored studies. Recruitment timelines (actual for completed studies, planned for ongoing) were a median of 20 and 31 months for phase 2 and phase 3 studies, respectively, reflecting a significant part of the overall development timeline of new drugs. Conclusions: The number of patients required for lupus studies has more than doubled in the last 6 years, primarily to meet drug development needs. As the number of sites engaged in lupus research is limited, drug development timelines are increasing to recruit the required number of patients to demonstrate efficacy and build adequate safety databases. Unless additional sites are deployed, the cost and time required to develop a drug for lupus may become prohibitive considering patent life restrictions and the advent of biosimilars. Novel approaches, e.g., adaptive trial designs and personalized medicine, are also required to facilitate ongoing drug development in lupus and ensure provision of new therapies. Disclosure of Interest: N. Goel Employee of: Quintiles, E. van Rijen Employee of: Quintiles, J. Hillier Employee of: Quintiles, R. Hepburn Employee of: Quintiles, A. Duncan Employee of: Quintiles DOI: 10.1136/annrheumdis-2014-eular.5307